Emotional activation in a cognitive behavioral setting: extending the tradition with embodiment - Hauke, Gernot; Lohr-Berger, Christina; Shafir, Tal (Frontiers in Psychology, 2024)
The neuroscience-based concept of "embodied cognition" or "embodiment" highlights that body and psyche are closely intertwined, i.e. effects of body and psyche are bidirectional and reciprocal. This represents the view that cognitive processes are not possible without the direct participation of the body. Traditional Cognitive Behavioral Therapy (CBT) addresses emotional processes on a conceptual level (dysfunctional thoughts, beliefs, attributions, etc.). However recent findings suggest that these processes already start at the level of bodily sensations. This opens up a way of working in therapy that includes the level of bodily sensations, where the development of emotional meaning is supported by bottom-up processes. Bidirectionality of embodiment can be effectively exploited by using body postures and movements associated with certain emotions, which we refer to as embodiment techniques, to deepen the physical experience of poorly felt emotions and support the valid construction of emotional meaning. This embodied approach offers several advantages: Prelinguistic or hard-to-grasp aspects can be identified more easily before being processed verbally. It is also easier to work with clients who have limited access to their emotions. Thus, in this paper we describe a new embodied CBT approach to working on the dysfunctional schema, which is based on three modules: body focus, emotional field, and interaction focus. In addition, using specific zones in the space of the therapy-room allows the embodiment of problematic interactions, as well as of power and powerlessness, closeness and distance, etc. Directly experiencing these processes on one's own body in the protected space of therapy allows faster and deeper insights than would be possible with conversations alone. Finally, the vitalizing power of emotions is used to create coherent action plans and successful interactions. This working method is illustrated by means of a case from practice.